Jordan Generalized (μ,ρ)-Reverse Derivation from - Nayef, Mahdi Saleh; Mahmood, Auday Hekmat; Salih, Salah Mehdi (Iraqi Journal of Science, 2021)
In this study, we introduce and study the concepts of generalized ( , )-reverse derivation, Jordan generalized ( , )-reverse derivation, and Jordan generalized triple ( , )-reverse derivation from Γ-semiring S into ΓS-module X. The most important findings of this paper are as follows: If S is Γ-semiring and X is ΓS-module, then every Jordan generalized ( , )- reverse derivations from S into X associated with Jordan ( , )-reverse derivation d from S into X is ( , )-reverse derivation from S into X.